Social identity and attitudes toward foreign policy: evidence from a youth survey in Turkey - Ciftci, Sabri (My University, 2013)
This paper focuses on the relationship between social identity based on national, religious, or international affiliations and attitudes toward foreign policy in the Turkish context. Evidence is drawn from an original survey conducted among university students in Turkey. The results show that students' social identity has a significant correlation with their perceptions of foreign policy. Most Turkish university students provide conditional support for the new directions in Turkey's foreign policy, but those with an Islamic identity appear to be more supportive of the Adalet ve Kalkınma Partisi's (Justice and Development Party) policies. Most university students believe that Turkey's future lies in the European Union and the Central Asian Turkic republics rather than in the Middle East. Overall, the perceptions of educated youth toward foreign policy are shaped by both social identity and their conceptions of national interest.
Keywords: Social identity; Foreign policy; Turkey